Raman chemical and physical mapping of oral dosage forms - Tres, Francesco (2015)
A high number of new chemical entities emerging from the drug development process show pharmacological activity, but at the same time are characterised by poor dissolution and solubility profiles. As a result, there is a strong push to develop innovative formulations for the delivery of such compounds so that the desired oral bioavailability and pharmacological effects are achieved. An increasingly popular class of formulations to improve the dissolution properties of poorly soluble drugs is represented by amorphous solid dispersions, whereby the drug is molecularly dispersed in a carrier matrix. One of the key challenges for developing amorphous solid dispersions in real-world formulations is the understanding of the dissolution performance. Although this is very important, due to the fact that the dissolution performance limits the in vivo efficacy, the dissolution mechanisms by which the amorphous solid dispersions dissolve is still not fully understood.